A model for predicting chatter stability considering contact characteristic between milling cutter and workpiece. Issue 5 (February 2017) - Yue, Caixu; Liu, Xianli; Liang, Steven
Abstract It has been demonstrated that chatter has a negative effect on machined surface quality during milling process. The identification of chatter is crucial for reducing its influence on machining integrity, especially for the milling process of curved surface. Change of cutter position will cause chip thickness to vary in milling process. Therefore, different contact characteristic between milling cutter and workpiece will be brought out. Compared with the traditional predictive model, a model for predicting chatter stability considering this contact characteristic is proposed in this study. Stability lobe diagrams at different cutter positions are proposed to predict milling stability by employing full-discrete method. A series of experiments are carried out to calibrate and verify the stable lobe diagram. The predicting result is in good agreement with experimental investigation for the stability characterization of curved surface milling process. The model proposed in this study could be used to improve machined quality for curved surface.